2016
DOI: 10.1016/j.eatbeh.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Meal patterning in the treatment of bulimia nervosa

Abstract: Objective This study examined the relationship between changes in meal and snack consumption and eating disorder behaviors in a treatment sample of bulimic adults. Method Eighty adults with bulimia nervosa (BN) were randomized to one of two treatments. Meal and snack consumption, binge eating frequency, and purging behavior frequency were assessed at baseline, end-of-treatment, and at four month follow-up using the Eating Disorder Examination (EDE). Results Generalized linear models indicated that increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…Studies specifically examining meal patterns in BN indicate that individuals with BN eat fewer meals, particularly lunches, than those with BED or no eating disorder, 13 and that regular evening meal consumption may be important for reducing binge eating and purging. 26 Our results with this Latina sample did not support these prior observations from research conducted with predominantly White female samples. We did observe differences in results between our BED and BN samples, with more frequent evening snack consumption being associated with greater weight and shape concerns, and less dietary restriction within the BN group only.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies specifically examining meal patterns in BN indicate that individuals with BN eat fewer meals, particularly lunches, than those with BED or no eating disorder, 13 and that regular evening meal consumption may be important for reducing binge eating and purging. 26 Our results with this Latina sample did not support these prior observations from research conducted with predominantly White female samples. We did observe differences in results between our BED and BN samples, with more frequent evening snack consumption being associated with greater weight and shape concerns, and less dietary restriction within the BN group only.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies specifically examining meal patterns in BN indicate that individuals with BN eat fewer meals, particularly lunches, than those with BED or no eating disorder, and that regular evening meal consumption may be important for reducing binge eating and purging . Our results with this Latina sample did not support these prior observations from research conducted with predominantly White female samples.…”
Section: Discussionmentioning
confidence: 99%
“…Regular eating has consistently been associated with decreased frequency of binge eating (Ellison et al, 2016; Shah, Passi, Bryson, & Agras, 2005; Waller, Evans, & Pugh, 2013; Wilson, Fairburn, Agras, Walsh, & Kraemer, 2002; Zendegui, West, & Zandberg, 2014). However, this is the first study to assess change in both variables on a weekly basis.…”
Section: Discussionmentioning
confidence: 99%
“…One reason many patients may fail to achieve remission from CBT for BN is suboptimal levels of therapeutic skill acquisition (ie, the ability to successfully perform a skill learned in treatment) and skill utilization (ie, the frequency with which a patient practices or uses therapeutic skills) [3,4]. Acquisition and utilization of therapeutic skills designed to reduce dietary restraint (eg, regular eating) consistently predict treatment outcomes [4][5][6][7]. In addition, numerous studies have demonstrated that reduction of dietary restraint is a key mechanism of action in CBT for BN [2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%